Hydrochemical and Isotopic Difference of Spring Water Depending on Flow Type in a Stratigraphically Complex Karst Area of South Korea - Yu, Soonyoung; Chae, Gitak; Oh, Junseop; Kim, Se-Hoon; Kim, Dong-Il; Yun, Seong-Taek (Frontiers in Earth Science, 2021)
Characterizing the subsurface flow in karstic areas is challenging due to distinct flow paths coexisting, and lithologic heterogeneity makes it more difficult. A combined use of hydrochemical, environmental isotopic, and hydrograph separation study was performed to understand the subsurface flow in a karst terrain where Ordovician carbonate rocks overlie Jurassic sandstone and shale along thrusts. Spring water collected was divided into Type Ⅰ (n = 11) and Ⅱ (n = 30) based on flow patterns (i.e., low and high discharge, respectively). In addition, groundwater (n = 20) was examined for comparison. Three Type Ⅱ springs were additionally collected during a storm event to construct hydrographs using δ18O and δD. As a result, Type Ⅱ had higher electrical conductivity, Mg2+, HCO3-, and Ca2+/(Na+ + K+) than Type Ⅰ and was mostly saturated with calcite, similar to deep groundwater. The hydrochemical difference between Types Ⅰ and Ⅱ was opposite to the expectation that Type Ⅱ would be undersaturated given fast flow and small storage, which could be explained by the distinct geology and water sources. Most Type Ⅱ springs and deep groundwater occurred in carbonate rocks, whereas Type Ⅰ and shallow groundwater occurred in various geological settings. The carbonate rocks seemed to provide conduit flow paths for Type Ⅱ given high solubility and faults, resulting in (1) relatively high tritium and NO3- and Cl- via short-circuiting flow paths and (2) the similar hydrochemistry and δ18O and δD to deep groundwater via upwelling from deep flow paths. The deep groundwater contributed to 83–87% of the discharge at three Type Ⅱ springs in the dry season. In contrast, Type Ⅰ showed low Ca2+ + Mg2+ and Ca2+/(Na+ + K+) discharging diffuse sources passing through shallow depths in a matrix in mountain areas. Delayed responses to rainfall and the increased concentrations of contaminants (e.g., NO3-) during a typhoon at Type Ⅱ implied storage in the vadose zone. This study shows that hydrochemical and isotopic investigations are effective to characterize flow paths, when combined with hydrograph separation because the heterogenous geology affects both flow paths and the hydrochemistry of spring water passing through each pathway.